Итоги и последствия мирового кризиса (Путеводитель предпринимателя, 2020)
As the main maintenance of article the substantiation of crash of liberal ideology under which influence the economy of the USA and Europe, and together with them and all world developed last decades serves. Present crisis - logic end of speculative model of economic growth and a dominating role of the financial capital. So change of model of capitalism - a key problem of the XXI-st century.